LOGIKA KEBAHAGIAAN MAHASANTRI DI PESANTREN (STUDI KASUS DI KAMPUS IDIA PRENDUAN SUMENEP MADURA) - Iwan Kuswandi (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2017)
The life of pesantren students (santri) are often connoted to simplicity in standing alone and live what it is worth. Although they live in simplicity, the mahasantri in IDIA Prenduan have happiness logic in their life. The blissfulness means a happiness that is felt by someone. Therefore, this research covered about the logic of happiness of mahasantri in IDIA Prenduan, and the factors of happiness that is enjoyed by mahasantri IDIA Prenduan. By qualitative descriptive method, found that they are happy in living at pesantren campus because they have new friends from all of corner Indonesian Archipelago. In addition, the existence of programs and learning systems that prioritize the lesson kepesantrenan (ma'hadi) and Islamic Shari'a are being a factor of happiness for mahasantri in IDIA Prenduan university.Â Togetherness in learning and worship also contribute to other factors of santri happiness. Moreover, the Kiai often raise the theme of gratitude in the lectures and lessons given by the Kiai in IDIA Prenduan. In addition, in the interest of education, IDIA Prenduan efforts to direct its santri to be the the patient and sincere person type. Sincerity is the soul of all branches of human belief and that result of it is the happiness.